Amphotericin B and anidulafungin directly interact with DNA and induce oxidative damage in the mammalian genome1. Issue 9 (11th September 2015) - Mandal, Santi M.; Chakraborty, Anirban; Hossain, Maidul; Mahata, Denial; Porto, William F.; Chakraborty, Ranadhir; Mukhopadhyay, Chinmay K.; Franco, Octavio L.; Hazra, Tapas K.; Basak, Amit
<x xml:space="preserve">Abstract</x> Amphotericin B and anidulafungin are widely used antifungal drugs for the treatment of systemic and serious mycoses.